2017
DOI: 10.1002/bkcs.11163
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tailed Metalloporphyrins Modified with 2‐Chloronicotinic Acid and Interactions with Human Serum Albumin

Abstract: Two kinds of free‐base tailed porphyrins modified with 2‐chloronicotinic acid and the corresponding Zn porphyrins have been synthesized. They have been characterized by elemental analysis and NMR, UV/Vis, fluorescence spectra, and infrared spectroscopies. Their configurations have been optimized through theoretical calculations. The fluorescence quantum yields were determined by a comparative method. The interactions between the Zn porphyrins and human serum albumin have been studied by means of fluorescence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In addition, the negative Gibbs free energy change (DG) reected the spontaneity of the interaction process. [39][40][41] The interaction forces were further analyzed using the simulation trajectory of different stages in the MD simulation process. As shown in the upper panel of Fig.…”
Section: Interaction Force Analysismentioning
confidence: 99%
“…In addition, the negative Gibbs free energy change (DG) reected the spontaneity of the interaction process. [39][40][41] The interaction forces were further analyzed using the simulation trajectory of different stages in the MD simulation process. As shown in the upper panel of Fig.…”
Section: Interaction Force Analysismentioning
confidence: 99%
“…DG < 0 indicated that the binding between pepsin and DFX molecules was spontaneous; DH < 0, DS < 0 indicated that the main force of pepsin and DFX molecule binding was the hydrogen bond. 28 3.2 The effects of interaction on the structure of pepsin 3.2.1 Synchronous uorescence spectroscopy. Synchronous uorescence can distinguish the overlapping peaks of endogenous uorescent chromospheres in the ordinary uorescence spectrum, so that the uorescence change of a single uorescent chromophore aer the addition of the quencher can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Δ G < 0 indicated that the binding between pepsin and DFX molecules was spontaneous; Δ H < 0, Δ S < 0 indicated that the main force of pepsin and DFX molecule binding was the hydrogen bond. 28 …”
Section: Resultsmentioning
confidence: 99%